Biological activity of local honey bees in growth of some gram positive and negative bacteria - G., Al-Mohana A.M. (The Iraqi Journal of Veterinary Medicine, 2012)
The local study was targeting to investigate the biological antibacterial activity for gradiate concentrations of a local honey bees (125,250, 375 and 500 mg/ml) were tested for five type of bacteria, two of which are gram positive (staphylococcusaureus , streptococcus spp.) and three of them were negative bacteria ( Esherichia coli , salmonella spp. , pseudomonas aeruginosa) by using agar well diffusion method and tube dilution method.The results of agar well diffusion method showed that the bacteria of Staphylococcus aureus and Streptococcus Spp. were the most sensitive to honey dilutions, while E.coli ,Salmonella Spp. showed moderate sensitivity . Pseudomonas aeruginosadid not show any sensitivity. The result also showed that the temperature of incubation temperature of culture media (25and 37 C) had a marked effect on the result of local study, outperformed of diameters of growth inhibition in the cultures that were incubated at 25 C in most of the result recorded.The result of the tube dilution method, Minimum Inhibition Concentration (MIC) was ( 8 , 8 , 125 and 64) mg/ml for the growth of S.aureus , Streptococcus , E.coli and salmonella respectively , while the Minimum Bactericidal Concentration (MBC) for bacteria mentioned were (32 , 64 , 250 and 250) mg/ml respectively for tubes that incubated at 25 C while tubes which incubated at 37 C MIC recorded (8 , 8 , 125 and 250) mg/ml while MBC were ( 32 , 64 , 125 and 250) mg/ml respectively.